Системність лінгвістичного аналізу при проведенні ідентифікаційних експертиз - Бардіна, Н.; Каташинська, І. (Лексикографічний бюлетень, 2006)
The modern linguistic criminalistic examination refers to the classical multilevel language model. Methodology based on the discourse model has been suggested for efficiency increase.